Perceived parental attitudes and the levels quality of life in children and adolescents at high risk for schizophrenia - PERDAHLI FİŞ, NEŞE (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2018)
Objective: The aims of this study were to compare the levels quality of life and perceived parental attitude in children and adolescents at high risk for schizophrenia with offspring of parents without any psychiatric disorder, and to investigate the factors affecting parental attitudes perceived by children and quality of life of children. Methods: The psychiatric assessments of parents with schizophrenia who have been followed up in the Community Mental Health Center and that of healthy parents were done by a psychiatrist. Diagnostic interview with the children, within the age range of 7-16 years, was conducted by a child psychiatrist. Children and adolescents were asked to fill out self-report scales relevant to perceived parental attitudes and quality of life. Results: The levels of emotional and social functioning and the levels of parental acceptance/interest were significantly lower in the high risk group when compared to the control group. Children in the high risk group defined their parents as 'negligent' at a higher rate than the control group. There was a significant effect of socio-demographic variables such as parental education level and paternal vocational status on the quality of life scores. When compared to children of fathers with schizophrenia, children of mothers with schizophrenia had much lower quality of life scores. The duration of parental illness and the duration of hospitalization were negatively correlated with the quality of life of children. Discussion: Our study demonstrated that offspring of parents with schizophrenia had a high risk of being neglected by their parents, and a decline in their quality of life, especially in the social and emotional aspects. Preventive interventions including development of positive relationships with their parents, are crucial for children at genetic high risk for schizophrenia.
Keywords: parent; schizophrenia; high risk; parental attitudes; quality of life; SERIOUS MENTAL-ILLNESS; MOTHERS; FAMILIES; PSYCHOPATHOLOGY; EXPERIENCES; DISORDERS; SPECTRUM; OUTCOMES